TBX22 mutation associated with cleft lip/palate, hypodontia, and limb anomaly - Kaewkhampa A. (2014)
Mutations in TBX22 are known causes of cleft palate with/without ankyloglossia. We identified a hemizygous missense c.452G>T (p.Arg151Leu) mutation in a Thai boy who had unilateral complete cleft lip and palate, agenesis of a maxillary second premolar, ankyloglossia, hypoplastic carpal bones, and hypoplastic right thumb. Our study has demonstrated that TBX22 mutation is associated not only with cleft palate and ankyloglossia, but also cleft lip and palate and tooth agenesis. Phenotypic variability caused by a single nucleotide substitution is clearly demonstrated.